On a coupled nonlocal nonlinear Schrödinger system. (November 2022) - Ji, Jia-Liang; Kai, Yue; Xu, Zong-Wei; Ma, Li-Yuan
Abstract: Recently, Ablowitz and Musslimani have introduced a new integrable nonlocal nonlinear Schrödinger equation. In this paper, we investigate an integrable coupled nonlocal nonlinear Schrödinger equation which can be derived from the AKNS system. The Darboux transformation is constructed for this equation. Via this Darboux transformation, we obtain its different kinds of exact solutions including soliton, kink, periodic solutions and so on. Dynamics and interactions of different kinds of soliton solutions are discussed. Finally, we compare the obtained results with standard coupled NLS equation. Highlights: Introduce a new coupled nonlocal nonlinear Schrödinger equation. Construct Darboux transformation and exact solutions for the equation. Interactions of different kinds of soliton solutions are discussed. Compare the obtained results with standard coupled nonlinear Schrödinger equation.